Improving the Ability to Recognize Number Symbols 1–10 Through the Fishing Numbers Game for Children Aged 4–5 Years. - Tutut Widi Lestari; Habib Hambali (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
The background of this study is the low ability of children aged 4–5 years in recognizing number symbols at TK Al Amin Kebanaran. This ability plays an important role in early cognitive development, which serves as the foundation for children’s numeracy readiness. The purpose of this study is to improve the ability to recognize number symbols through the fishing numbers game.This research applied the Classroom Action Research (CAR) method and was conducted in two cycles. The study involved 21 children aged 4–5 years as research subjects. Data were collected through observation using instruments that included the ability to sequence, mention, imitate, and match number symbols with the quantity of objects.The results showed that the average percentage of children’s ability to recognize number symbols increased from 50.25% in the pre-cycle to 69.75% in Cycle I, and further increased to 81.75% in Cycle II. Improvements occurred across all ability indicators. Based on these findings, it can be concluded that the fishing numbers game is effective in improving the ability to recognize number symbols in children aged 4–5 years.